2019
DOI: 10.3390/toxins11050264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subcutaneous Ochratoxin-A Exposure on Immune System of Broiler Chicks

Abstract: Ochratoxin A (OTA), an immunosuppressive mycotoxin, can increase the risk of many infectious diseases and contribute to economic losses to the poultry industry. The immunosuppressive effect has mainly been investigated through oral exposure; however, birds may also be contaminated through skin absorption. The present study investigated the influence of OTA exposure on the defense system of broiler chicks through the subcutaneous route and including low doses. Groups of broiler chicks (Cobb), 05 days old, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…The inclusion of the additive in the mycotoxin contaminated feed, led to a reduction in the number of monocytes that could indicate less intestinal inflammation, which would represent a beneficial effect for chickens. It has been described that subcutaneous OTA exposure increased levels of monocytes in broiler chickens [ 31 ]. Other blood parameters were not affected by dietary treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of the additive in the mycotoxin contaminated feed, led to a reduction in the number of monocytes that could indicate less intestinal inflammation, which would represent a beneficial effect for chickens. It has been described that subcutaneous OTA exposure increased levels of monocytes in broiler chickens [ 31 ]. Other blood parameters were not affected by dietary treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that OTA or T-2 mycotoxin could affect the immune system by the atrophy of the lymphoid organs along with depletion of lymphocytes and the enlargement of the kidney and liver [ 9 , 13 , 31 ]. However, in the current research, the combination of OTA and T-2 mycotoxin at levels examined in broilers feed did not affect the relative weights of liver, gizzard, kidneys, and spleen ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins can also cause atrophy and failure of immune organs and other histopathological changes [ 98 ]. Khan et al significantly detected leucopenia and the decrease of IgY and IgA concentrations in serum, as well as the weightlessness of thymus, spleen, and bursa in chicks after OTA exposure [ 99 ]. To sum up, mycotoxin exposure can induce immunosuppression.…”
Section: Major Toxicity Mechanisms Induced By Mycotoxins and Heavy Me...mentioning
confidence: 99%
“…Similarly, corticosterone decreases the weights of the primary immune organs, thymus and bursa Fabricius, in birds (e.g., young chickens: Mehaisen et al, 2017 ). Spleen weights are also decreased following exposure to toxicants (Aflatoxin B 1 : Grozeva et al, 2017 ; Ochratoxin A: Khan et al, 2019 ; T-2 toxin: Hayes and Wobeser, 1983 ) (see Table 6 ). In contrast, spleen weights were increased after viral challenges or administration of E. coli lipopolysaccharide (see Table 6 ) ( Boa-Amponsem et al, 1999 ; Zhang et al, 2017 ; Bai et al, 2019 ; Yang et al, 2019 ).…”
Section: Immune Systemmentioning
confidence: 99%